Pengaruh Rasio Likuiditas dan Rasio Solvabilitas Terhadap Pertumbuhan Laba Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Subsektor Makanan dan Minuman di BEI Periode 2017-2021 - Lestiana, Jihan (Universitas Prof.Hazairin,SH Bengkulu, 2022)
This study aims to determine how the effect of the liquidity ratio proxied into Current Ratio and solvency ratio proxied into Debt to Total Assets on profit growth partially or partially. Simultaneously with additional moderating variables, namely company size, which will strengthen or weaken the relationship between the Current Ratio and Debt to Total Assets on profit growth in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This study uses quantitative research methods with an associative approach. The research population was 26 companies and 14 companies were used as research samples with a sample selection technique using purposive sampling technique. The results showed that partially or t-test Current Ratio has a significant negative effect on profit growth. Then the Debt to Total Assets has no significant effect on profit growth. Meanwhile, simultaneously Current Ratio and Debt to Total Assets have a positive effect on profit growth. Then, the moderating variable shows that company size cannot moderate the relationship between Current Ratio and Debt to Total Assets on company profit growth.